Resistance Mechanisms of the Metastatic Tumor Microenvironment to Anti-Angiogenic Therapy - Schiffmann, Lars M.; Bruns, Christiane J.; Schmidt, Thomas (Frontiers in Oncology, 2022)
Angiogenesis describes the formation of blood vessels from an existing vascular network. Anti-angiogenic drugs that target tumor blood vessels have become standard of care in many cancer entities. Though very promising results in preclinical evaluation, anti-angiogenic treatments fell short of expectations in clinical trials. Patients develop resistance over time or are primarily refractory to anti-angiogenic therapies similar to conventional chemotherapy. To further improve efficacy and outcome to these therapies, a deeper understanding of mechanisms that mediate resistance to anti-angiogenic therapies is needed. The field has done tremendous efforts to gain knowledge about how tumors engage tumor cell and microenvironmental mechanisms to do so. This review highlights the current state of knowledge with special focus on the metastatic tumor site and potential therapeutic relevance of this understanding from a translational and clinical perspective.